Pretrichodermamide C and N-methylpretrichodermamide B, two new cytotoxic epidithiodiketopiperazines from hyper saline lake derived Penicillium sp. (March 2015) - Orfali, Raha S.; Aly, Amal H.; Ebrahim, Weaam; Abdel-Aziz, Mohamed S.; Müller, Werner E.G.; Lin, WenHan; Daletos, Georgios; Proksch, Peter
Graphical abstract: Highlights: We isolated a Penicillium sp. from the sediment of a hyper saline lake in Egypt. The cultured fungus afforded two new epidithiodiketopiperazine derivatives. The structures were determined by extensive analysis of the spectroscopic data. The compounds were tested against the murine lymphoma L5178Y cell line. Abstract: Two new epidithiodiketopiperazines, pretrichodermamide C (1 ) and N-methylpretrichodermamide B (2 ) were isolated from the fungus Penicillium sp., derived from the sediment of a hyper saline lake located at Wadi El-Natrun in Egypt. The structures of1 and2 were unambiguously determined on the basis of one- and two-dimensional NMR spectroscopy and by high-resolution mass spectrometry, as well as by comparison with the literature. Compound2 showed pronounced cytotoxicity against the murine lymphoma L5178Y cell line with an IC50 value of 2 μM.